Partie orientale du Canada, avec la Nouvelle Angleterre, L'Acadie, et la Terre-Neuve - Anville, Jean Baptiste Bourguignon d', 1697-1782 (Venice, 1776)
Hand coloured. Decorative title cartouche. Relief shown pictorially. Bar scales in Italian and English miles. CNS map no. 219. -- Plate no., upper right: P. 11; original plate no. "47" partly erased.